Normosmic idiopathic hypogonadotropic hypogonadism due to a novel homozygous nonsense c.C969A (p.Y323X) mutation in the KISS1R gene in three unrelated families - CESUR, YAŞAR; DEMIRBILEK, Huseyin; OZBEK, M. Nuri; DEMIR, Korcan; KOTAN, LEMAN DAMLA; Cesur, YAŞAR; Dogan, Murat; Temiz, Fatih; Mengen, Eda; GÜRBÜZ, FATİH; YÜKSEL, BİLGİN; Topaloglu, A. Kemal (My University, 2015)
ObjectiveThe spectrum of genetic alterations in cases of hypogonadotropic hypogonadism continue to expand. However, KISS1R mutations remain rare. The aim of this study was to understand the molecular basis of normosmic idiopathic hypogonadotropic hypogonadism.